The Moment I wake a documentary film exploring the phenomenon of sleep paralysis in the Filipino context - Armas, Mark Leonard M.; Tañedo, Jose Alberto (Quezon City University of the Philippines Diliman, 2017)
The objectives of the research are to determine the cause, debunk the misconceptions about the phenomenon of sleep paralysis, and to provide information as to how the victims of sleep paralysis will be able to stop or prevent it from happening. For the scope and limitation, the study will focus on bangungot as sleep paralysis and not as another meaning such as mere nightmare or the extreme, which is death during sleep. The informative perspective will be focused on the medical professionals and sleep doctors, and not on superstitious, paranormal, or spiritual perspectives on the phenomenon.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 59-60
Keywords: Sleep paralysis; Sleeping disorders; Stress